The source of the Canary Current in fall 2009 - Pérez Hernández, María Dolores; Hernández Guerra, Alonso; Fraile Nuez,Eugenio; Comas Rodríguez, I.; Benítez Barrios, V.M.; Domínguez Yanez, J.F.; Vélez Belchí,Pedro; Armas, Demetrio de (2014)
The source of the Canary Current has been inferred from an inverse box model applied to the hydro- graphic data of a survey carried out in 2009 in the northeast subtropical gyre (29–37ºN, 9–24ºW). The Portugal Current is observed between 13.5 and 14.8ºW at 37ºN carrying 1.8±0.4 Sv southward. This current presumably merges with the eastward transport of the Azores Current System and partly contributes to the Mediterranean inflow and partly to the northward recirculation of the Azores Current through the Gulf of Cadiz. The Azores Current System is located in the meridional range 33.50–36.25ºN at 24.50ºW. This System transports eastward 7.2±0.5 Sv in the thermocline layers and 1.1±0.8 Sv at intermediate layers. The Azores Current intermediate water mass has the highest portion of Sub-Arctic intermediate water (SAIW) in the region, while the Azores Countercurrent intermediate waters mass is mainly Mediterranean water. The Canary Current extends from 22.25º to 18.50ºW at 29ºN, the westernmost position ever observed. This current transports southward -6.2±0.6 Sv in the thermocline layers and -2.0±0.8 Sv in the intermediate layers. This intermediate flow shows a relative maximum of oxygen and a relative minimum in nutrient concentration, indicating the presence of SAIW. The study concludes that, at least in fall 2009, the Canary Current extends to the intermediate waters (γn 27.9220 approximately 1600 dbar) and that Azores Current feeds the Canary Current at surface and intermediate layers. 459 459 1